Barriers for Implementing Concrete Recycling in Small Construction Projects. Issue 1 (February 2021) - Darof, A C; Rahman, R A; Zakaria, Z; Yusof, NA
Abstract: Recycling addresses environmental issues associated with solid waste by minimizing overall resource consumption and environmental impact. In the construction industry, concrete recycling is crucial because concrete is the most dominant waste of construction and demolition waste. However, its implementation is at a low level in numerous countries, including Malaysia because project managers refuse to adopt concrete recycling in practice. Detailed information is needed to find the obstacle to recycle concrete waste, including often neglected small construction projects. This study's objective is to identify factors that are affecting decisions in adopting concrete recycling from project managers' perspective. Nine barriers to implementing concrete recycling in Malaysia are identified. The nine barriers can be associated with facilities, the workforce, quality, financial, technologies, and resources. This research contributes to the body of knowledge is in the analysis of factors that influence the acceptance of concrete recycling from industry practitioners' perspectives, which could help researchers and industry practitioners develop strategies to reduce the rejection of concrete recycling among project managers. The findings of this research would help improve the success of adopting concrete recycling in the construction industry.